A study of a preventive dental program for pregnant women and their offspring (0-3years) - กัลยาสิริ, เกษม; คําซื้อ, ชูจิตร (Thai Dental Public Health Journal, 2008)
The aim of this study was to evaluate the effects of a preventive dental program for pregnant women and their offspring starting during pregnancy. 428 pregnant women from ante-natal clinic at Health Promoting Hospital, Bangkok participated in phase one. In phase two (at 6 age) 211 of mother-child couples and in the end of the study (at 3 year of age) 51 couples of the mother - child remained. In phase one the dental problems of the pregnant women were treated and their toothbrushing skills were adjusted during the visits scheduled for ante-natal care and their offspring's birth weight were recorded. In phase two the offspring were examined and monitored for early childhood caries during the visits scheduled for vaccination while mothers were given repeated oral hygiene instruction of childhoods as well as being supplied with oral nd a hand on practicing of the mothers to brush their children's teeth Results: in phase 1 the pregnant women revealed significant improvement in oral health through dental treatments and as shown by their tooth brushing test score and plaque score had improved. In phase two, additionally in the area of general health the rate of low birth weight of the study group (3.45) lower than the annual rate of this hospital (7.39). and the rate of caries free of the study group at 3 years of age (72.54) was significantly higher than that of the control group (42.85). The results suggest that the program may significantly improve the oral health of mother and child.